THE ROLE OF CULINARY TOURISM NOSTALGIA ON THE TOURIST SATISFACTION MODEL: THE STIMULUS-ORGANISM-RESPONSE APPROACH - Wahyudi, Lilik; Ahmad, Ana Shohibul Manshur Al; Sarjiyanto, Sarjiyanto; Sarwoto, Sarwoto (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
Tourist satisfaction and tourism destinations create a value for tourists. The value of specific tourism destinations leads to individual emotional attachments, which are a manifestation of a sense of nostalgia. This study aims to investigate the role of nostalgia on the tourist satisfaction at culinary tourism destinations. Food quality, destination environment, and services all contribute to the nostalgia. The data was collected through LimeSurvey from a total of 300 respondents from Central Java and Yogyakarta and was analyzed using PLS-SEM. The results show that the food quality, destination environment, and services positively affect the nostalgia. Further, the nostalgia also has a strong significant influence on the tourist satisfaction. These findings imply that managers of culinary tourism must be able to provide positive values (impressions) to the tourists by offering unique service, quality, or destination environment compared to other destinations. It is expected that the tourists have a positive memorability which simultaneously create a revisit intention, which is in line with the tourists satisfaction.JEL:D91, D90, Z32.